Comparing general and regional anesthesia in patients undergoing primary total hip arthroplasty: analysis of national health insurance data in Korea - Seungyoung Lee; Eunjin Ahn; Eunjin Ahn; Min Kyoung Kim; Min Kyoung Kim; Fletcher A. White; Fletcher A. White; Euiheon Chung; YongHun Chung; YongHun Chung (Frontiers in Medicine)
ObjectivesTo compare the effects of general and regional anesthesia on clinical outcomes following primary total hip arthroplasty (THA).MethodsThis retrospective study using data from the Korean National Health Insurance Research Database included 1,522 patients who underwent THA under general anesthesia (n = 640) or regional anesthesia (n = 882) between 2002 and 2015. We compared the mortality and complication rates within 30 days after surgery.ResultsProsthesis failure (1.56% vs. 0.45%, p = 0.025), admission to the intensive care unit (9.53 vs. 5.44%, p = 0.0023), and total cost (₩7,332,515 vs. ₩6,833,295, p < 0.0001) were higher in the general anesthesia group than in the regional anesthesia group. No significant differences were observed in mortality (0.94% vs. 0.57%, p = 0.54), transfusion rate (81.1% vs. 80.9%, p = 0.94), length of hospital stay (45 vs. 45 days, p = 0.23), or other complications between the groups. Similar results were observed in propensity-score matched analysis (n = 640 patients per group).ConclusionOur study showed that both anesthesia types resulted in comparable mortality and complication rates in patients who underwent THA, but the costs differed.